STRUCTURAL MODEL OF THE EFFECT OF FUNCTIONAL AND NONFUNCTIONAL ATTRIBUTES OF M-COMMERCE APPLICATIONS ON USABILITY AND CONTINUANCE USAGE INTENTION - Antoni Hutahaean, Hotma
Mobile commerce (m-commerce), a special form of e-commerce, has become a growing trend in recent years. M-commerce can be defined as the buying and selling of goods and services online with the support of mobile devices. The development of m-commerce applications often results in complex systems with many functional features in the user interface. However, many features do not always have a positive impact from the perspective of user experience related to Usability and impersonality. Usability is the extent to which a product can be used by a particular user to achieve a specified goal. A high level of Usability can encourage customers to use the application continuously, thereby encouraging users to become loyal. The attributes that form Usability value include functional and non-functional attributes. Functional attributes refer to the ability of the application to support the achievement of specific goals. Meanwhile, non-functional attributes are related to the quality of the system in supporting the overall user experience. Although both types of attributes are very important, currently research that uses functional and non-functional attributes simultaneously in one model is very limited. This study aims to build a structural model that analyzes the relationship between functional and non-functional attributes simultaneously, towards Usability and continued use intention. Based on the analysis model, this study recommends functional and non-functional indicators and attributes that are prioritized for improvement. The originality and new contribution of this study is the use of functional and non-functional attributes of m-commerce applications simultaneously, as well as the analysis of the relationship between usability and continuance usage intention. The methodology used in this study is quantitative and qualitative methods for the development model. Model development was carried out by literature study and qualitative methods in the form of interviews for the development of the initial research model using 11 attributes. Furthermore, a survei was conducted on 295 respondents using purposive sampling to identify user perceptions. Model testing and analysis were carried out using the Part Least Square Structural Equation